Design and Construction of a Low-Cost Combat Robot - Costa, R. B.; Itacaramby, G.; Cabral, J.; Pastrana, M. A.; Peñaloza, J. M.; Muñoz, Daniel M. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
This paper presents the design and construction of a low-cost combat robot named Artemis, developed for participation in the Robocore Experience 2024 competition. The project emphasizes the integration of cost-effective components and innovative methodologies to create a competitive robot. The ESP32 microcontroller was selected for its advantages in energy efficiency and connectivity, surpassing traditional platforms like Arduino. The construction process involved several phases, including planning, development, testing, correction, and performance evaluation, utilizing tools such as CAD software for design and 3D printing for fabrication. Key components included a DC motor, L298N H-bridge, and a LiPo battery, all chosen to optimize performance while adhering to budget constraints. The robot's design evolved through iterative testing and adjustments, ultimately leading to a successful competition debut. This work highlights the importance of resourcefulness and collaboration in robotics, showcasing how educational institutions can foster innovation in engineering projects.